The role of automated external defibrillators in rural general practice. - Hanley, K (1999)
In a questionnaire survey (100% response rate) investigating the availability and use of automated external defibrillators (AEDs), it was found that the success rate (number discharged alive) compared favourably with pre-hospital defibrillation by other providers, and that AEDs aided the management of dysrhythmias not commonly seen in general practice. With appropriate training they are useful in rural general practice.